2020
DOI: 10.3390/molecules25061274
|View full text |Cite
|
Sign up to set email alerts
|

1H-NMR Metabolomics Analysis of the Effect of Rubusoside on Serum Metabolites of Golden Hamsters on a High-Fat Diet

Abstract: Rubusoside is a natural sweetener and the active component of Rubus suavissimus. The preventive and therapeutic effect of rubusoside on high-fat diet-induced (HFD) serum metabolite changes in golden hamsters was analyzed by 1H-NMR metabolomics to explore the underlying mechanism of lipid metabolism regulation. 1H-NMR serum metabolomics analyses revealed a disturbed amino acid-, sugar-, fat-, and energy metabolism in HFD animals. Animals supplemented with rubusoside can partly reverse the metabolism disorders i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…RS contains diterpene compounds such as rubusoside -a natural sweetener which is 115 times sweeter than sucrose, avonoids, polyphenols, and triterpenoid compounds [13][14][15][16]. Recent research showed that the total extract of RS, the polyphenols of RS, or puri ed rubusoside affect lipid metabolism disorder and improve the obesity phenotype [17], hyperlipidemia, or reduce blood lipid content and blood pressure [18][19][20]. However, the exact molecular mechanism still remains unknown.…”
Section: Introductionmentioning
confidence: 99%
“…RS contains diterpene compounds such as rubusoside -a natural sweetener which is 115 times sweeter than sucrose, avonoids, polyphenols, and triterpenoid compounds [13][14][15][16]. Recent research showed that the total extract of RS, the polyphenols of RS, or puri ed rubusoside affect lipid metabolism disorder and improve the obesity phenotype [17], hyperlipidemia, or reduce blood lipid content and blood pressure [18][19][20]. However, the exact molecular mechanism still remains unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Serum pyruvate is derived from alanine and a-ketoglutarate converted by the alanine aminotransferase (ALT) and elevated ALT is a diagnostic marker for liver injury. The concentration of serum pyruvate was also elevated by high-fat diet intake [42]. 1,3-Dihydroxyacetone is a 3-carbon reducing sugar produced from glycerol.…”
Section: Discussionmentioning
confidence: 99%
“…Myristic acid also found to have altered band distribution in our analysis, is a long-chain saturated fatty acid, abundant in milk and derivatives ( Verruck et al, 2019 ), and a known cargo of exosomes ( Subra et al, 2010 ). It can be associated with an increase in exosome transportation of myristic acid and the myristic acid concentration is thought to be related to hypertensive disease ( Li et al, 2020 ). In addition, it was described that reduced myristic acid levels are associated with the onset of preeclampsia ( Villa et al, 2009 ; Paik et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%